Determination of the market value for goods in the process of forensic commodity expertise - L. A. Solonichenko; D. Yu. Sereda (Bulletin of Kharkiv National University of Internal Affairs)
The article deals with the important issue of determining the market value of goods in forensic commodity expertise. This process is crucial for ensuring the objectivity of court decisions in commercial and civil disputes. The study focuses on the development of methodological approaches that allow obtaining accurate valuation results despite economic instability and unpredictable market changes.